PEBERDAYAAN KEMAMPUAN BERORGANISASI DI KALANGAN SANTRI PONPES MIFTAHUL ULUM PANDEAN WONOREJO BANYUPUTIH SITUBONDO - Nur Ainiyah (As-Sidanah, 2021)
This outreach program aimed to train students in achieving organizational skills, management, leadership and communication skills. It was located in Miftahul Ulum Islamic Boarding School. Based on the result of the interview data and documentation, it shows that: the organizational activities of the Miftahul Ulum Islamic Boarding School students include the management structure and the head of the division who is responsible for each position; students carry out activities by focusing more on learning objectives; meeting involve activity planning, activity actualization, activity arrangement and activity controlling are carried out once a month with a facilitator.